Identification of Levothyroxine Antichagasic Activity through Computer-Aided Drug Repurposing - Carolina L. Bellera; Darío E. Balcazar; Lucas Alberca; Carlos A. Labriola; Alan Talevi; Carolina Carrillo (The Scientific World Journal)
Cruzipain (Cz) is the major cysteine protease of the protozoan Trypanosoma cruzi, etiological agent of Chagas disease. A conformation-independent classifier capable of identifying Cz inhibitors was derived from a 163-compound dataset and later applied in a virtual screening campaign on the DrugBank database, which compiles FDA-approved and investigational drugs. 54 approved drugs were selected as candidates, 3 of which were acquired and tested on Cz and T. cruzi epimastigotes proliferation. Among them, levothyroxine, traditionally used in hormone replacement therapy in patients with hypothyroidism, showed dose-dependent inhibition of Cz and antiproliferative activity on the parasite.